The Use of Plastic Plates in Place of Discs in The Material of Throwing Discs for Grade VI Students of SD Negeri 84 Kendari - Wa Sakita (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
The purpose of this study was to determine the effectiveness of the use of plastic plate media in the subject matter of discus throwing students of class VI Negeri 84 Kendari. This study uses two rounds of action research. Each cycle consists of two stages: design, activity, observation, and reflection. The target of this research is the students of class VI Negeri 84 Kendari, amounting to 35 students. The research data were obtained in the form of the results of the practice test for throwing discs. The results of the analysis showed that students were able to throw discs in the first cycle for male students (85%) and female students (70%) and in the second cycle for male students (97.5%) and female students (75%). This study using plastic plate media can have a positive effect on the ability to throw discs for students of class VI Negeri 84 Kendari and this learning media can be used as an alternative to discus throwing subject matter.